2019
DOI: 10.1002/cncy.22148
|View full text |Cite
|
Sign up to set email alerts
|

Atypical cytological changes mimicking SIL of the uterine cervix in allogenic hematopoietic stem cell transplantation recipients treated with busulfan

Abstract: BACKGROUND: Allogenic hematopoietic stem cell transplantation (allo-HSCT) is a common procedure in hematological disorders and is preceded by a conditioning regimen that usually includes busulfan. The immunosuppression caused by the conditioning regimen and graft-versus-host disease prophylaxis is associated with human papillomavirus (HPV) persistence and, consequently, with an increased risk of cervical cancer (CC) and squamous intraepithelial lesions (SILs)-the precursors of CC. A gynecological check-up that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Most of the literature regarding abnormal cervical cytology has been reported in the era before primary HPV testing, although a recent study reported a 26.7% risk of abnormal cervical cytology in patients with GVHD, all of whom were HPV-negative 34 . Another recent report confirmed a similar frequency of abnormal cervical cytology especially in patients with a diagnosis of genital GVHD 17 .…”
Section: Resultsmentioning
confidence: 97%
“…Most of the literature regarding abnormal cervical cytology has been reported in the era before primary HPV testing, although a recent study reported a 26.7% risk of abnormal cervical cytology in patients with GVHD, all of whom were HPV-negative 34 . Another recent report confirmed a similar frequency of abnormal cervical cytology especially in patients with a diagnosis of genital GVHD 17 .…”
Section: Resultsmentioning
confidence: 97%